2014
DOI: 10.4103/0972-124x.147410
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of C-reactive protein in peripheral blood of patients with healthy gingiva, gingivitis and chronic periodontitis: A clinical and particle-enhanced turbidimetric immuno-analysis

Abstract: Background:C-reactive protein (CRP), an acute-phase protein monitored as a marker of inflammatory status, has been identified as a major risk factor for various systemic diseases. It is a reliable marker to infectious burdens and/or inflammation. The aim of this study was to compare and evaluate the systemic levels of CRP in the serum sample of the patients with healthy gingiva, gingivitis, and chronic periodontitis.Materials and Methods:A total of 60 systemically healthy patients were selected and divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
0
19
1
2
Order By: Relevance
“…As for other chronic inflammatory diseases, the relationship be- observed between gingivitis and the other periodontal conditions did not consistently reach statistical significance in all studies. [184][185][186] In subjects with gingivitis, the severity and extent of gingival inflammation were evaluated for their relationship with CRP levels in serum. While in some studies CRP levels were found to be significantly positively correlated with papillary bleeding index 186 or GI, 184 other authors failed to find an association between CRP levels and GI, 185 BOP, 185,187 or the number of sextants with at least one BOP+ site.…”
Section: Systemic Inflammation Markers (Crp)mentioning
confidence: 99%
“…As for other chronic inflammatory diseases, the relationship be- observed between gingivitis and the other periodontal conditions did not consistently reach statistical significance in all studies. [184][185][186] In subjects with gingivitis, the severity and extent of gingival inflammation were evaluated for their relationship with CRP levels in serum. While in some studies CRP levels were found to be significantly positively correlated with papillary bleeding index 186 or GI, 184 other authors failed to find an association between CRP levels and GI, 185 BOP, 185,187 or the number of sextants with at least one BOP+ site.…”
Section: Systemic Inflammation Markers (Crp)mentioning
confidence: 99%
“…The patients with gingivitis and healthy gingiva had lower levels of CRP than the patients with chronic periodontitis. Furthermore, with increasing inflammation, the high-sensitivity CRP levels increased proportionately [ 18 ]. It is possible to use CRP in prediction and early detection of periodontal disease [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systemic host immune-inflammatory response against periodontal pathogens is indicated by the presence of antibodies against periodontal pathogens, such as Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola (Poole et al, 2013 ; Noble et al, 2014 ). Additionally, patients diagnosed with periodontitis present higher levels of inflammatory mediators in serum, such as C-reactive protein (CRP) in patients with chronic periodontitis (Bansal et al, 2014 ; Ardila and Guzmán, 2015 ), and leptin in patients with aggressive periodontitis (Shi et al, 2015 ). It has been suggested that the periodontal infection and the immuno-inflammatory response against periodontal pathogens may increase the host susceptibility to systemic diseases, including osteoporosis (Martelli et al, 2017 ), diabetes mellitus (Hanes and Krishna, 2010 ; Otomo-Corgel et al, 2012 ; Preshaw et al, 2012 ), cancer (Martelli et al, 2017 ), autoimmunity and cardiovascular disease (Page, 1998 ; Friedewald et al, 2009 ; Pejcic et al, 2011 ; Otomo-Corgel et al, 2012 ; Martelli et al, 2017 ), dementia (Pazos et al, 2016 ) and neurodegenerative diseases such as AD (Kamer et al, 2008 , 2015 ; Rogers, 2008 ; Kubota et al, 2014 ; Gaur and Agnihotri, 2015 ; Ganesh et al, 2017 ; Sochocka et al, 2017a ).…”
Section: Contribution Of Periodontitis For Neuroinflammation and Disementioning
confidence: 99%